234k views
2 votes
Find:For f(x) = 5x – 2 and g(2) = 4xa) (f - g)(x) =wb) (f-9)(-3) =

Find:For f(x) = 5x – 2 and g(2) = 4xa) (f - g)(x) =wb) (f-9)(-3) =-example-1

1 Answer

1 vote

We have functions f and g defined as:

f(x) = 5x - 2

g(x) = 4x - 2

We can subtract both functions:

f(x) - g(x) = (5x - 2) - (4x - 2) = 5x - 2 - 4x + 2

Then:

f(x) - g(x) = x

But, by definition, we know that:

(f - g)(x) = f(x) - g(x)

Putting these together:

(f - g)(x) = x

Now, if x = -3:

(f - g)(-3) = -3

User Adam Magyar
by
5.1k points